Early weight trends after congenital heart surgery and their determinants. (26th December 2019) - Banerji, Nayan; Sudhakar, Abish; Balachandran, Rakhi; Sunil, Gopalraj Sumangala; Kotayil, Brijesh P.; Krishna Kumar, Raman
Abstract: Background: Early weight trends after cardiac surgery in infants from low- and middle-income countries where the majority are undernourished have not been defined. We studied the early post-operative weight trends to identify specific factors associated with early weight loss and poor weight gain after discharge following congenital heart surgery in consecutive infants undergoing cardiac surgery at a referral hospital in Southern India. Methods: This was a prospective observational study. Weights of the babies were recorded at different time points during the hospital stay and at 1-month post-discharge. A comprehensive database of pre-operative, operative, and post-operative variables was created and entered into a multivariate logistic regression analysis model to identify factors associated with excessive early weight loss after cardiac surgery, and poor weight gain following hospital discharge. Results: The study enrolled 192 infants (mean age 110.7 ± 99.9 days; weight z scores − 2.5 ± 1.5). There was a small but significant (p < 0.001) decline in weight in the hospital following surgery (1.6% decline (interquartile range −5.3 to +1.7)); however, there was substantial growth following discharge (26.7% increase (interquartile range 15.3–41.8)). The variables associated with post-operative weight loss were cumulative nil-per-oral duration and cardiopulmonary bypass time, while weight gain following discharge was only associated with age. Conclusion: Weight loss is almost universal early after congenital heart surgery and is associated with complex surgery and cumulative nil-per-oral duration. After discharge, weight gain is almost universal and not associated with any of the perioperative variables.